Jump-landing mechanics in patellar tendinopathy in elite youth basketballers - Harris, M.; Schultz, A.; Drew, M. K.; Rio, E.; Charlton, P.; Edwards, S. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Patellar tendinopathy (PT) is a leading cause of morbidity in jump-landing athletes. Landing mechanics are identified as a factor associated with PT and/or patellar tendon abnormality. This study aimed to identify key jump-landing variables associated with PT. Thirty-six junior elite basketball players (men n = 18, women n = 18) were recruited from a Basketball Australia development camp. Three-dimensional (3D) kinematic and ground reaction force (GRF) data during a stop-jump task were collected as well as ultrasound scans of the patellar tendons and recall history of training load data. Mixed-model factorial analyses of variance were used to determine any significant between-group differences. Of the 23 participants included for statistical analyses, 11 had normal bilateral patellar tendons (controls) and eight reported PT (currently symptomatic); however, the four participants categorized as asymptomatic with patellar tendon abnormality on diagnostic imaging were excluded from statistical analyses due to their small sample size. Athletes with PT displayed a similar knee flexion angle at initial foot-ground contact (IC) and hip extension strategy during a stop-jump horizontal landing. Despite a similar kinematic technique, athletes with PT utilized a strategy of a longer stance duration phase from IC to peak force. This strategy did not lead to those athletes with PT decreasing their peak vertical GRF nor patellar tendon force during landing but enabled these athletes to land with a lower rate of loading (control 59.2 ± 39.3 vs. PT 29.4 ± 33.7 BW.s-1). Athletes with PT still reported significantly reduced training volume (control 4.9 ± 1.8 vs PT 1.8 ± 1.1 sessions/wk; total training time/wk control 2.4 ± 1.0 vs PT 1.4 ± 1.1 h/wk).